2019
DOI: 10.3390/rs11242948
|View full text |Cite
|
Sign up to set email alerts
|

A Weighted SVM-Based Approach to Tree Species Classification at Individual Tree Crown Level Using LiDAR Data

Abstract: Tree species classification at individual tree crowns (ITCs) level, using remote-sensing data, requires the availability of a sufficient number of reliable reference samples (i.e., training samples) to be used in the learning phase of the classifier. The classification performance of the tree species is mainly affected by two main issues: (i) an imbalanced distribution of the tree species classes, and (ii) the presence of unreliable samples due to field collection errors, coordinate misalignments, and ITCs del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Some studies have suggested that the accuracy of tree species detection using multispectral or hyperspectral data could improve when combined with LiDAR data [31][32][33]. However, multispectral or hyperspectral data have many constraints in their acquisition and require complex data processing [34]. In this case, the spectral information included in very high-resolution UAV-DAP data would be a cost-effective alternative data source.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the accuracy of tree species detection using multispectral or hyperspectral data could improve when combined with LiDAR data [31][32][33]. However, multispectral or hyperspectral data have many constraints in their acquisition and require complex data processing [34]. In this case, the spectral information included in very high-resolution UAV-DAP data would be a cost-effective alternative data source.…”
Section: Introductionmentioning
confidence: 99%
“…Brandtberg [19] used LiDAR to classify individual tree species under leaf-off and leaf-on conditions and the accuracy of major species are around 60%. Nguyen et al [20] presented a wSVM-based approach for major tree species classification at ITC level using LiDAR data in a temperate forest and the accuracy was over 70%. Obviously, using LiDAR only is difficult to obtain high quality individual tree species, but multispectral LiDAR largely improves this condition by add spectral information to point cloud.…”
Section: Introductionmentioning
confidence: 99%
“…The normalized lidar point cloud were used to delineate individual tree crowns (ITCs) by means of Dalponte and Coomes' [46] algorithm implemented in the itcLiDAR function of the R library itcSegment. This algorithm is based on an adaptive local maxima filter and a region-growing method, and it has been successfully used in many previous studies [47][48][49][50]. The algorithm follows these steps: (1) generate a raster canopy height model (CHM) of spatial resolution defined by the user; (2) apply a Gaussian low-pass filter of fixed size of 3 × 3 pixels to the rasterized CHM in order to smooth the surface and to reduce the number of potential local maxima; (3) apply a moving window of variable size to the smoothed CHM in order to find a set of potential treetops (local maxima).…”
Section: Lidar Data Processingmentioning
confidence: 99%
“…Tree species classification and bark beetle attack detection were carried out using a class-weighted support vector machine (wSVM) classifier [49]. SVM is a well-known classifier that has been widely used in many studies in forestry and ecology [49,[72][73][74].…”
Section: Tree Species Classification and Bark Beetle Detectionmentioning
confidence: 99%
See 1 more Smart Citation